2008
DOI: 10.2174/187152008785914743
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Approaches to Anti-Cancer Chemotherapeutics

Abstract: Numerous proteins responsible for cell proliferation and differentiation exist either as hetero or homodimers or become activated through dimerization as a key step in their respective signaling cascade. Many of these proteins have been identified as major components in oncogenic signaling pathways and have become popular targets for the development of anti-tumor agents. For this reason, bivalent anti-cancer drugs that could potentially interact with each monomer of a dimeric protein target have been developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 84 publications
0
35
0
1
Order By: Relevance
“…Dimers of apigenin linked with ethylene glycol linker showed enhanced anticancer effect compared to apigenin in multidrug resistance breast cancer cells as well as in leukemia cell lines (Zhang et al 2004). It was suggested that dimeric molecules could bind to two distinct sites on a single molecule or a defined site on two separate molecules (Hadden and Blagg 2008). With respect to A" peptide aggregation and toxicity, a dimeric polyphenol, curcumin ( Fig.…”
Section: Beneficial Roles Of Naturally Occurring Polyphenolic Compounmentioning
confidence: 99%
“…Dimers of apigenin linked with ethylene glycol linker showed enhanced anticancer effect compared to apigenin in multidrug resistance breast cancer cells as well as in leukemia cell lines (Zhang et al 2004). It was suggested that dimeric molecules could bind to two distinct sites on a single molecule or a defined site on two separate molecules (Hadden and Blagg 2008). With respect to A" peptide aggregation and toxicity, a dimeric polyphenol, curcumin ( Fig.…”
Section: Beneficial Roles Of Naturally Occurring Polyphenolic Compounmentioning
confidence: 99%
“…Polyvalent molecules have the potential to yield nonlinear, multifold potency against their respective targets compared to their corresponding monomers (18, 19). With the goal of generating new autophagy inhibitors with better potency, tolerability, and anticancer efficacy than HCQ, we used logical medicinal chemistry approaches to generate a series of new dimeric compounds containing modified core elements of HCQ, CQ and the anti-schistosomal drug lucanthone (Miracil D) (20).…”
Section: Introductionmentioning
confidence: 99%
“…The most effective are coumermycin A1 (CA1) and its analogs (Figure 2). 20, 26, 27 There is currently no data on how the C-terminal hsp90 inhibitor CA1 controls the immunophilins. However, work done by Ratajczak and co-workers showed that a millimolar concentration of a structurally similar C-terminal inhibitor, novabiocin, disrupts immunophilins from binding to hsp90.…”
mentioning
confidence: 99%